SYARIâAH DALAM PERSPEKTIF PELAKU BISNIS MLM SYARIâAH AHADNET INTERNASIONAL ( Studi Kasus di Kota Semarang ) - Huda, Choirul (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2013)
PT. Ahadnet International, a business Multi Level Marketing (MLM) Syariah, is a MLM business operations based on the principles of syariah . The business attracted many people from among Muslims because it offers businesses with marketing Islamic halal products and toyyib. No doubt, many Muslims were later merged into the Ahadnet MITRANIAGA. Nevertheless, the Muslims interests of this business does not mean not raising the issue. Labeling the word âSyariahâ is attached to the naming MLM International Syariâah Ahadnet it needs proper interpretation. Wrong interpretation of the word shariah for the Ahadnet International MLM syariâah business will bring counterproductive, both for the company, MITRANIAGA and for Islam itself. Seeing this phenomenon, it is through this study, researchers are trying to see how far the understanding of the actors (MITRANIAGA) International Ahadnet the term shariâah. Their understanding of Shariâah will affect the way they work on the syariah business in genera,Â particularly MLM syariâah business